Implementation of Government Accounting Policies for the Preparation of Financial Statements in the Indonesian Army - Muharram Belle; M. Baharudin Zubakhrum Tjenreng (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the implementation of government accounting policies based on the accrual-based Government Accounting Standards in the preparation of financial statements within the Indonesian Army. The research employs a descriptive qualitative approach through in-depth interviews, document analysis, and limited observations. The findings indicate that the implementation of government accounting policies has been formally carried out through the application of the Institutional-Level Financial Application System. However, the implementation still faces several challenges, including limited human resources with an adequate understanding of accrual-based accounting concepts, technical issues within the system, and a lack of coordination among work units involved in preparing financial statements. Furthermore, the review function conducted by the Internal Government Supervisory Apparatus of the Indonesian Army has not fully addressed the substantive aspects of accounting. These findings are consistent with the policy implementation theories of Mazmanian & Sabatier and Van Meter & Van Horn. This study recommends enhancing human resource competencies, optimizing the use of financial systems, and strengthening the role of the Internal Government Supervisory Apparatus to improve the quality of financial statements, ensuring greater transparency and accountability.